Evaluation of Treatment Adherence and Uncontrolled Blood Sugar Prevalence in Type 2 Diabetes Mellitus Patients at a Tertiary Care Centre in Rajnandgaon, Chhattisgarh, India. - Rohit David; Daneshwer Singh; Harshal Mendhe (Global Journal of Medicine and Public Health, 2025)
ABSTRACT Background Diabetes mellitus is a growing global health challenge, with diabetic peripheral neuropathy (DPN) emerging as one of its serious complications. DPN contributes significantly to morbidity, including debilitating pain, foot ulcers, and increased risk of amputation, particularly among populations with limited healthcare resources. Methods A descriptive, cross-sectional study was conducted at the Government Medical College Hospital in Rajnandgaon, involving 203 patients aged 21 years and above with type 2 diabetes mellitus (T2DM) diagnosed for at least one year. The Michigan Neuropathy Screening Instrument (MNSI) was employed to assess DPN, and socio-demographic along with clinical data were systematically collected. Data analysis using SPSS revealed associations between DPN and various risk factors. Results The prevalence of DPN among the study cohort was substantial. Statistical evaluation indicated significant correlations between the presence of neuropathy and factors such as prolonged duration of diabetes, advanced age, and suboptimal glycemic control. These findings highlight the vulnerability of diabetic patients to nerve damage over time due to sustained metabolic imbalances. Conclusions The considerable prevalence of DPN underscores the critical need for routine screening and early intervention in diabetic care, particularly within resource-constrained settings. Implementing standardized diagnostic tools like the MNSI can facilitate timely detection and management, thereby reducing complications and improving quality of life. Tailored healthcare strategies focused on optimal glycemic control are essential to address the socio-economic and clinical challenges posed by DPN.